Effects of uterine cervix constriction on Wistar rats - Raposo-Amaral, Cassio Eduardo; Almeida, Ana Beatriz; Raposo-Amaral, Cesar Augusto; Vulcano, Luiz Carlos [UNESP]; Passos-Bueno, Maria Rita; Alonso, Nivaldo (FapUNIFESP (SciELO), 2010)
Purpose: To verify if uterine cerclage can induce craniosynostosis or any cranial deformity in new born Wistar rats. Methods: One pregnant female Wistar rat underwent laparotomy on day 18 of gestation and the uterus cervix was closed with a 3-0 nylon suture to avoid delivery, that occurs normally on the 21 day. The suture was released after 48 hours beyond the normal gestation period. The female rat delivered 11 pups. Six surviving rats from the delivery (group A - constrained group). Two rats were born from another mother and in the same age were used as control group (group B - 2 nonconstrained controls) were allowed to grow. They were sacrificed 1.2 years after their birth all the eight animals. Linear measurement, routine histology and computed tomography of the skull were performed at the time of their death to evaluate the cranial asymmetries by mesurements of the anatomical landmarks of the craniofacial skeleton of the rats on the two groups and compared then. Results: We did not observe statistically significant differences in any of the compared measurements (p>0.05) obtained through the morphologic and radiologic methods. Histologic examinations did not reveal any sign of premature fusion or suture imbrications. Critical decrease in longitudinal body size was noticed as the limbs too in all the animals of group A. Conclusion: Constriction of uterine cervix leads to fetus suffering, even death for a few animals, associated to small body size, but not to craniosynostosis.
Keywords: Cerclage, cervical; Craniosynostoses; Rats; Surgery, plastic